Antibiotics Prescription Over Three Years in a French Benchmarking Network of 23 Level 3 Neonatal Wards - Martin-Mons, Séverine; Lorrain, Simon; Iacobelli, Silvia; Gouyon, Béatrice; Gouyon, Jean-Bernard; , On behalf of the B-PEN Study Group (Frontiers in Pharmacology, 2021)
Introduction: Prescribing antibiotics to newborns is challenging, as excess antibiotics are a risk factor for increased morbidity and mortality. The objective of this study was to describe the evolution of antibiotic exposure over three years in a large network of level 3 neonatal wards where each center is informed yearly of its own results, the results of other centers, and has full autonomy to improve its performance. Patients and Methods: A prospective, observational study of antibiotics prescriptions over the 2017-2019 period in a network of 23 French level 3 neonatal wards. The network relied on an internal benchmarking program based on a computerized prescription ordering system. Among others, antibiotics exposure, treatment duration, and antibiotics spectrum index were analyzed. Results: The population consisted of 39,971 neonates (51.5% preterm), 44.3% of which were treated with antibiotics. Of the treated patients, 78.5% started their first antibiotic treatment in the first three days of life. Antibiotic exposure rate significantly declined from 2017 to 2019 (from 46.8% to 42.8%, p<0.0001); this decline was significant in groups with gestational age >26 weeks, but not in the group with extremely low gestational age <27 weeks. Gentamicin, cefotaxime, amoxicillin (ampicillin), vancomycin, and amikacin were the antibiotics most prescribed. The lower the gestational age, the higher the exposure for cefotaxime, vancomycin, and amikacin. Compared to 2017, cefotaxime exposure in 2019 declined by 12.6%, but the change was only significant in the gestational age group of 32-36 weeks (17.4%) and at term (20.3%). The triple combination of antibiotics in the first three days decreased by 28.8% from 2017 to 2019, and this was significant in each gestational age group. During the study, the delayed ending of antibiotics in unconfirmed early-onset neonatal infection increased from 9.6% to 11.9%. Conclusion: This study showed that a strategy characterized by the collection of information via a computerized order-entry system, analysis of the results by a steering committee representative of all neonatal wards, and complete autonomy of neonatal wards in the choice of prescription modalities, is associated with a significant reduction in the use of antibiotics in newborns with gestational age greater than 26 weeks.